This is the question:
Use strong mathematical induction to prove that for any integer n≥2, if n is even, then any sum of n odd integers is even, and if n is odd, then any sum of n odd integers is odd.
I know that P(n) is the sentence:
“If n is even, then any sum of n odd integers is even, and if n is odd, then any sum of n odd integers is odd.”
If anyone could guide me a bit or provide some sort of formula, it be much appreciated!
Answer
The first step is
to get this into
mathematical form.
I would write it like this:
Let
(ai)ni=1
be odd integers.
Then,
for any positive integer m,
∑2mi=1ai
is even
and
∑2m−1i=1ai
is odd.
Proof.
Note:
All variables are integers.
The basic facts needed are that
(1) every even number a
can be written in the form
a=2b;
(2) every odd number a
can be written in the form
a=2b+1;
(3) all numbers are either
even or odd;
(4) the sum of two even numbers
is even;
(5) the sum of an odd and even integer
is odd;
(6) the sum of two odd numbers
is even.
Note:
Facts (1) and (2)
are definitions.
A good exercise is
to prove facts
(3) through (6).
For m=1,
this states that
a1 is odd and
a1+a2 is even.
The first is true by assumption.
The second is true because
the sum of two odd integers
is even.
For the induction step,
suppose it is true for m.
The statement for
m+1 is
∑2(m+1)i=1ai
is even
and
∑2(m+1)−1i=1ai
is odd.
For the first,
∑2(m+1)i=1ai=∑2m+2i=1ai=∑2mi=1ai+a2m+1+a2m+2=(∑2mi=1ai)+(a2m+1+a2m+2)
and this is even
(using fact 4) because
∑2mi=1ai
is even by the induction hypothesis
and
a2m+1+a2m+2
is even by fact 6.
For the second,
∑2(m+1)−1i=1ai=∑2m+1i=1ai=∑2m−1i=1ai+a2m+a2m+1=(∑2m−1i=1ai)+(a2m+a2m+1)
and this is odd
(using fact 5) because
∑2m−1i=1ai
is odd by the induction hypothesis
and
a2m+a2m+1
is even by fact 6.
You could also group the sum as
∑2mi=1ai+a2m+1;
in this,
the sum is even
and a2m+1
is odd,
so their sum is odd.
No comments:
Post a Comment